Transformation of University Financial Governance Towards Financial Independence in the Digital Era: A Systematic Literature Review - Samsul Hadi; Fitriyana Fitriyana; Evi Gusliana; Undang Rosyidin (Indonesian Journal of Education and Youth Development, 2026)
This study investigates the transformation of higher education financial governance as institutions transition toward financial independence in an increasingly digital and market-driven landscape. Utilizing a Systematic Literature Review (SLR) of scholarship from 2014 to 2024, the research synthesizes global and national perspectives, with a particular focus on the Indonesian context, to identify strategies for revenue diversification and the role of digital innovation. Findings indicate that the shift from bureaucratic-administrative to managerial-entrepreneurial models is essential for institutional resilience. Key strategies include the optimization of endowment funds, research commercialization, and Public-Private Partnerships (PPP). Furthermore, the integration of Enterprise Resource Planning (ERP) systems and Financial Technology (FinTech), such as blockchain for auditing, significantly enhances transparency and accountability. The study concludes that achieving financial autonomy requires a holistic alignment of robust governance frameworks, digital infrastructure, and public transparency to ensure long-term fiscal sustainability.